The Influence of Finasteride on the Development of Prostate Cancer - Thompson, Ian M; Goodman, Phyllis J; Tangen, Catherine M; Lucia, M. Scott; Miller, Gary J; Ford, Leslie G; Lieber, Michael M; Cespedes, R. Duane; Atkins, James N; Lippman, Scott M; Carlin, Susie M; Ryan, Anne; et al. (The New England journal of medicine, 2003)
This randomized trial tested the idea that finasteride, which inhibits the production of androgens within the prostate, can prevent prostate cancer. The participants were to receive finasteride or a placebo daily for seven years. Prostate cancer was found in 18.4 percent of the men in the finasteride group and in 24.4 percent of those in the placebo group. Higher-grade cancers (Gleason score, 7, 8, 9, or 10) were more common in the finasteride group than in the placebo group. Sexual dysfunction was more common in the finasteride group, and urinary difficulties were more common in the placebo group. A test of the idea that finasteride can prevent prostate cancer. To date, the management of prostate cancer, the most common nondermatologic neoplasm in men in the United States, has focused on early diagnosis and treatment. Given that the development of prostate cancer is a long-term process involving multiple steps, however, prevention may be a more effective approach. There is abundant evidence that androgens influence the development of prostate cancer. 1 – 3 The development of finasteride, an inhibitor of steroid 5α-reductase, the enzyme that converts testosterone to the more potent androgen dihydrotestosterone, created an opportunity to test the possibility that lowering the androgen levels in the prostate would reduce the risk of . . .